Lựa chọn các ngành kinh tế quan trọng và có lợi thế so sánh ở Việt Nam - Võ Tất , Thắng; Nguyễn Thị Bích, Hiền; Trần Mỹ , Huyền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The article uses location quotient analysis and Shift - Share analysis to identify five key industries in Vietnam, including: Manufacturing, construction, accommodation - food services, commerce, and agriculture-forestry-fisheries. The results show that manufacturing, construction, and accommodation - food services are "standout" industries that define national characteristics and have development potential. While commerce and agriculture-forestry-fisheries industries are large in scale, their competitive advantages have been gradually weakening over time. When compared with other ASEAN countries, Vietnam has advantages in scale and labor specialization in manufacturing, construction, and accommodation - food services, however, labor productivity remains low compared to other countries in the region. The study then forecasts the GDP development of these industries during the 2024–2030 period. Drawing from lessons and experiences of developed countries like the Netherlands, China, Germany, Taiwan, and the United Kingdom, the research proposes appropriate development solutions and policies for each industry in Vietnam, focusing on improving productivity, technology integration, and sustainable development.
Keywords: Important industries; Comparative advantages; Shift - Share analysis; Location quotient analysis; Regional economy